Influence of Student’s Characteristics on the Preferences and Availability of Student Housing in Tembalang Higher Education Area (HEA) - Sekar Kharisma Ardhia Prastiwi; Santy Paulla Dewi (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2023)
Tembalang Higher Education Area (HEA) has rapidly developed since the existencing of Diponegoro University in 2010. The constantly increasing number of students occured demands this area to fulfill the housing needs of its students. Availability of housing that doesn’t match their demand can lead to vacant housing which losses for various parties. As the housing consumers, students with various characteristics play an important role on this process. Therefore, the purpose of this study is to find out the influence of students characteristics towards their preferences for housing needs and its availability in HEA of Tembalang. These influences are analyzed using quantitative research methods with multiple linear regression and quantitative descriptive. The results of the study indicate that student’s hometown and study year have a significant effect on the preference of student's housing type by 31%, while the study year, transportation and student’s activities have a significant effect on the preference of student's housing location by 10.2%. Refer to the influences explained, this study predicted that student housings with HMO and private housing types on Bulusan and Kramas Village will develop significantly, where through this development, housing vacancies phenomenon can be avoided